Processing duplicates in the activities of the Rumyantsev Museum library in 1920-s - E. A. Jemeljanova (Библиосфера, 2013)
On the basis of archival documents stored in the collection of the Russian state library, the problems related to the distribution of books received by the Rumyantsev museum after the October revolution 1917 from the nationalized state, public and private book collections are studied.